Keabsahan dan Kekuatan Pembuktian Tanda Tangan Digital dalam Transaksi E-Commerce - Chandra Johan Alen; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The growth of e-commerce has transformed private law agreements and evidence through electronic signatures (E-signatures). Despite recognition under the UU ITE, classifications of certified and uncertified E-signatures and their evidentiary value still pose normative and practical challenges. This normative juridical research applies statutory, conceptual, and case approaches to analyze the regulation, validity requirements, evidentiary strength, and implementation challenges of E-signatures to ensure legal certainty and party protection. Primary legal sources include the Indonesian Civil Code, UU ITE, PP 71/2019, and Permenkominfo 11/2022. The results show that E-signatures are legally valid if they meet Article 11 of the UU ITE and PP 71/2019. Their evidentiary value equals other electronic evidence, though their weight depends heavily on authentication, system integrity, and Electronic Certification Provider reliability. E-signature effectiveness in court ultimately relies on technical standardization, digital-legal literacy, and consistent evidentiary practices.